FORMATION OF DIDACTIC COMPETENCE OF FUTURE PHYSICAL EDUCATION TEACHERS - Tkachivska, Inna; Serman, Taras; Prezliata, Hanna (Mountain School of Ukrainian Carpaty, 2022)
The article deals with the peculiarities of the formation of didactic competence of future physical education teachers in the conditions of modern educational realities. The didactic competence of the future physical education teacher is an important component of his professional readiness, which provides at the personal level his self -organization in accordance with professional requirements and enables to professionally carry out pedagogical activity in the system of physical culture of the educational institution. The basic ideas of the competence approach are analyzed and systematized, on the basis of which the model of didactic competence of the future physical culture teacher, consisting of three components: motivational-information, cognitive-content and technological. The motivational and information component was aimed at the formation of stable motivation for students to thoroughly study pedagogical didactics as a factor of realization of acquired knowledge and skills in the pedagogical activity of the future teacher of physical culture. This is facilitated by the involvement of students in active forms of classes: presentations, heuristic conversations, cognitive games, debates, symposia. The cognitive-content component is directed to the formation of completeness of theoretical knowledge and features of practical application of different forms of work. The study of educational topics involves the widespread use of active forms of work: modeling, presentations, "brainstorming", candid conversations, symposia, debates, protection of didactic models developed by students. The technological component involved acquaintance of students with different methods and features of developmental learning. The developed model of didactic competence with its content filling is implemented during the teaching of the discipline "Pedagogy of physical culture with the basics of didactics". It is investigated that the formation of didactic activity of students of specialty 014 Secondary education (physical culture) is possible with the implementation of structural content components on the basis of cross-curricular integration with professional-oriented disciplines and the widespread use Interest in pedagogical didactics and develop reflexive abilities. Keywords: didactic competence, future physical culture teachers, physical culture pedagogy.